Transcriptome profiling of Paracoccidioides brasiliensis yeast-phase cells recovered from infected mice brings new insights into fungal response upon host interaction - Costa, Milce; Borges, Clayton L.; Bailao, Alexandre M.; Meirelles, Gabriela V.; Mendonca, Yuri A.; Dantas, Sabrina F. I. M.; de Faria, Fabricia P.; Felipe, Maria S. S.; Molinari-Madlum, Eugenia E. W. I.; Mendes-Giannini, Maria José Soares [UNESP]; Fiuza, Rogerio B.; Martins, Wellington S.; et al. (Soc General Microbiology, 2007)
Paracoccidioides brasiliensis is a fungal human pathogen with a wide distribution in Latin America. It causes paracoccidioidomycosis, the most widespread systemic mycosis in Latin America. Although gene expression in P. brasiliensis had been studied, little is known about the genome sequences expressed by this species during the infection process. To better understand the infection process, 4934 expressed sequence tags (ESTs) derived from a non-normalized cDNA library from P. brasiliensis (isolate Pb01) yeast-phase cells recovered from the livers of infected mice were annotated and clustered to a UniGene (clusters containing sequences that represent a unique gene) set with 1602 members. A large-scale comparative analysis was performed between the UniGene sequences of P. brasiliensis yeast-phase cells recovered from infected mice and a database constructed with sequences of the yeast-phase and mycelium transcriptome (isolate Pb01) (https://dna.biomol.unb.br/Pb/), as well as with all public ESTs available at GenBank, including sequences of the P. brasiliensis yeast-phase transcriptome (isolate Pb18) (http:// www.ncbi.nlm.nih.gov/). The focus was on the overexpressed and novel genes. From the total, 3184 ESTs (64.53%) were also present in the previously described transcriptome of yeast-form and mycelium cells obtained from in vitro cultures (https://dna.biomol.unb.br/Pb/) and of those, 1172 ESTs (23.75% of the described sequences) represented transcripts overexpressed during the infection process. Comparative analysis identified 1750 ESTs (35.47% of the total), comprising 649 UniGene sequences representing novel transcripts of P. brasiliensis, not previously described for this isolate or for other isolates in public databases. KEGG pathway mapping showed that the novel and overexpressed transcripts represented standard metabolic pathways, including glycolysis, amino acid biosynthesis, lipid and sterol metabolism. The unique and divergent representation of transcripts in the cDNA library of yeast cells recovered from infected mice suggests differential gene expression in response to the host milieu.